Experimental models for the autoimmune and inflammatory blistering disease, Bullous pemphigoid - Leighty, Lisa (Springer-Verlag, 2007)
Bullous pemphigoid (BP) is a subepidermal skin blistering disease characterized immunohistologically by dermal-epidermal junction (DEJ) separation, an inflammatory cell infiltrate in the upper dermis, and autoantibodies targeted toward the hemidesmosomal proteins BP230 and BP180. Development of an IgG passive transfer mouse model of BP that reproduces these key features of human BP has demonstrated that subepidermal blistering is initiated by anti-BP180 antibodies and mediated by complement activation, mast cell degranulation, neutrophil infiltration, and proteinase secretion. This model is not compatible with study of human pathogenic antibodies, as the human and murine antigenic epitopes are not cross-reactive. The development of two novel humanized mouse models for the first time has enabled study of disease mechanisms caused by BP autoantibodies, and presents an ideal in vivo system to test novel therapeutic strategies for disease management.